2021
DOI: 10.1111/1477-9552.12424
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effects of Seasonal Tariff‐rate Quotas on Vegetable Prices in Switzerland

Abstract: Causal estimation of the short-term effects of tariff-rate quotas (TRQs) on vegetable producer prices is hampered by the large variety and different growing seasons of vegetables and is therefore rarely performed. We quantify the effects of Swiss seasonal TRQs on domestic producer prices of a variety of vegetables based on a difference-in-differences estimation using a novel dataset of weekly producer prices for Switzerland and neighbouring countries. We find that TRQs increase prices of most vegetables by mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…The exchange rate liberalisation in Russia in 2014 was introduced on a Saturday, so issues regarding midweek policy activations (e.g. [54] ) could be avoided. The described data processing allowed the collection of the minimum number of observations around the cut-off to meet the identifiability and positivity assumptions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The exchange rate liberalisation in Russia in 2014 was introduced on a Saturday, so issues regarding midweek policy activations (e.g. [54] ) could be avoided. The described data processing allowed the collection of the minimum number of observations around the cut-off to meet the identifiability and positivity assumptions.…”
Section: Methodsmentioning
confidence: 99%
“…A mass treatment effect of exchange rate liberalisation on trade withdraws the opportunity to find untreated import flows for difference-in-differences e . The regression discontinuity design appears to be useful for policy effect estimation (see the examples in [53,54] ) in the mentioned conditions, as it entails local regression, which requires the available data for Russian markets. The RDD was developed for individual data and requires adoption to study prices in time.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Data of higher frequency is required if changes occur within the period or aggregation level of one observation. This is particularly the case when analyzing season‐sensitive policies (e.g., Loginova et al., 2021). Usually, the higher the selected frequency, the narrower are the confidence intervals for estimations.…”
Section: Options Of Measure Selectionmentioning
confidence: 99%
“…The change in a number of observations may help fulfil the common trend assumption; however, if the estimated effects and their significance differ largely with the introduction of a couple of new observations, robustness of the model is failed. A time of structural break is sometimes excluded from data to avoid the influence of the transition period on the estimates (e.g., Loginova et al., 2021). Propensity score matching allows pairing observations from treated and control groups by similar values of characteristics (see the discussion in Caliendo & Kopeinig, 2008).…”
Section: Modeling Of Stabilitymentioning
confidence: 99%
“…Santos et al, (2015) focus on the maximization of vegetable farmers' income, and the study finds that it makes full use of the diverse harvesting period and productivity of crops and rotates different vegetable varieties to increase income [26]. Scholars have found that the GATT has an impact on EU fruit and vegetable policies [27], and then found that seasonal tariff quotas have led to fluctuations in vegetable prices [28]. Therefore, different import and export systems will directly affect the entry of vegetables into the market [29].…”
Section: Analysis Of Vegetable Price Fluctuation and Transmissionmentioning
confidence: 99%